Quantitative ultrasound to monitor the vascular response to tocilizumab in giant cell arteritis. (2nd October 2021) - Seitz, Luca; Christ, Lisa; Lötscher, Fabian; Scholz, Godehard; Sarbu, Adela-Cristina; Bütikofer, Lukas; Kollert, Florian; Schmidt, Wolfgang A; Reichenbach, Stephan; Villiger, Peter M
Abstract: Objectives: To characterize the effect of ultra-short glucocorticoids followed by Tocilizumab monotherapy on the intima-media thickness (IMT) in GCA. Methods: Eighteen GCA patients received 500 mg for 3 consecutive days (total of 1500mg) i.v. methylprednisolone on days 0–2, followed by i.v. Tocilizumab (8 mg/kg) on day 3 and thereafter weekly s.c. Tocilizumab injections (162 mg) over 52 weeks. US of temporal (TAs), axillary (AAs) and subclavian (SAs) arteries was performed at baseline, on days 2–3, and at weeks 4, 8, 12, 24 and 52. The largest IMT of all segments and IMT at landmarks of AA/SA were recorded. IMT was scaled by mean normal values and averaged. Each segment was classified according to diagnostic cut-offs. Results: Of the 18 GCA patients, 16 patients had TA and 6 had extracranial large artery involvement. The IMT showed a sharp decline on day 2/3 in the TAs and AAs/SAs. In TAs, this was followed by an increase to baseline levels at week 4 and a subsequent slow decrease, which was paralleled by decreasing symptoms and achievement of clinical remission. The AAs/SAs showed a new signal of vasculitis at week 4 in three patients, with an IMT increase up to week 8. Conclusion: Glucocorticoid pulse therapy induced a transient decrease of the IMT in TAs and AAs/SAs. Tocilizumab monotherapy resulted in a slow and steady decrease in IMT of the TAs and a smaller and delayed effect on the AAs/SAs. The data strongly support a remission-inducing effect of Tocilizumab and argue the case for US having an important role in monitoring disease activity in GCA. Trial registration: ClinicalTrials.gov, www.clinicaltrials.gov, NCT03745586.